Human Endogenous Retroviruses Are Ancient Acquired Elements Still Shaping Innate Immune Responses - Grandi, Nicole; Tramontano, Enzo (Frontiers in Immunology, 2018)
About 8% of our genome is composed of sequences with viral origin, namely human Endogenous Retroviruses (HERVs). HERVs are relics of ancient infections that affected the primates’ germ line along the last 100 million of years, and became stable elements at the interface between self and foreign DNA. Intriguingly, HERV co-evolution with the host led to the domestication of activities previously devoted to the retrovirus life cycle, providing novel cellular functions. For example, selected HERV envelope proteins have been coopted for pregnancy-related purposes, and proviral Long Terminal Repeats participate in the transcriptional regulation of various cellular genes. Given the HERV persistence in the host genome and its basal expression in most healthy tissues, it is reasonable that human defenses should prevent HERV-mediated immune activation. Despite this, HERVs and their products (including RNA, cytosolic DNA and proteins) are still able to modulate and be influenced by the host immune system, fascinatingly suggesting a central role in the evolution and functioning of the human innate immunity. Indeed, HERV sequences had been major contributors in shaping and expanding the interferon network, dispersing inducible genes that have been occasionally domesticated in various mammalian lineages. Also the HERV integration within or near to genes encoding for critical immune factors has been shown to influence their activity, or to be responsible for their polymorphic variation in the human population, such as in the case of an HERV-K(HML10) provirus in the major histocompatibility complex region. In addition, HERV expressed products have been shown to modulate innate immunity effectors, being therefore often related on the one side to inflammatory and autoimmune disorders, while on the other side to the control of excessive immune activation through their immunosuppressive properties. Finally, HERVs have been proposed to establish a protective effect against exogenous infections. The present review summarizes the involvement of HERVs and their products in innate immune responses, describing how their intricate interplay with the first line of human defenses can actively contribute either to the host protection or to his damage, implying a subtle balance between the persistence of HERV expression and the maintenance of a basal immune alert.